AGASTACHE FOENICULUM - A PERSPECTIVE SOURCE OF MEDICAL PRODUCTS - V. V. Chumakova; O. I. Popova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
A phytochemical study has been conducted to explore Agastache foeniculum (Lamiaceae), which is widely used in oriental medicine for colds, inflammation of the gastrointestinal tract and urinary system; exter-nally for fungal dermatitis, seborrhea, hair growth and strengthening. In the course of the experiment methods of chemical (such as alkalimetry, permanganatometriya, chelatometry) and physico-chemical (such as mass spec-trometry coupled with GC, differential UV spectrophotometry, HPLC, planar chromatography) analysis have been applied. The established range of biologically active compounds, especially essential oils and phenolic compounds, indicates the possibility of using Agastache foeniculum herb as a raw material source for producing drugs with antioxidant, antimicrobial, antimycotic and pilotropnym effect